Maximum voltage angle optimization of uninterruptible power supply on three-level transformer-less photovoltaic inverter - Muhammad Irwanto; Mohd Irwan, Yusoff; Gomesh Nair, Shasidharan; Noor Syafawati, Ahmad (Institute of Electrical and Electronics Engineers (IEEE), 2013)
Link to publisher's homepage at http://ieeexplore.ieee.org/